CLINICAL CASE OF LYMPHEDEMA AS A COMPLICATION OF CAT SCRATCH DISEASE - Mateiko, Halyna; Matvisiv, Mariana; Antoniuk, Liybov; Horbal, Nataliia; Hlushko, Uliana (Eastern Ukrainian Medical Journal, 2026)
Introduction. Cat scratch disease (CSD) is zoonotic infectious disease caused by the bacterium Bartonella henselae. Domestic cats, which are infected by fleas are the primary source of this infection. In humans, the disease occurs through contact with an infected animal, as a result of a bite or scratch. Difficulties in diagnosis are associated with the variety of clinical symptoms and lack of doctors’ alertness, especially in cases of atypical disease forms. Lymphadenopathy is the basis for differential diagnosis of CSD with neoplastic processes. The aim of the study: to focus doctors' attention on the possibility of an atypical subclinical course of CSD by analyzing a clinical case of the disease in the patient with lymphedema of the lower extremity. Materials and methods. The clinical examination results, laboratory and instrumental tests of a 35-year-old woman were analyzed. Case presentation. A 35-year-old woman consulted her family doctor with complaints of severe swelling of the left lower extremity, which had been bothering her for several months. Edema appeared in perfect health and gradually spread from the foot to the thigh.On examination, the left lower limb is swollen throughout. The diameter of the left lower leg is 4 cm larger than the right one, and the left thigh is 2.5 cm larger than the right one. In the left inguinal region, lymph nodes are visible and palpable, sensitive to palpation - 1.5-2 cm in size, dense, in the right inguinal region - up to 1 cm, not dense and not sensitive to palpation.The family doctor referred the patient to a vascular surgeon. After an ultrasound examination of the veins of the lower extremities, a complete blood count, no pathology of the veins of the lower extremities, and no other disorders were detected. The diagnosis was made: “Lymphedema of the left lower limb of unknown etiology”. The patient was referred to the regional oncology center to exclude oncological pathology. Based on the results of MRI and CT of the chest, abdominal cavity, and pelvic organs oncological pathology was excluded. Excision of the left inguinal lymph node with histopathological examination was performed, the results of which meet the histological criteria of benign lymphoreticulosis with fibrosis. When the patient was examined by an infectious diseases specialist, the doctor found out the details of the medical history: in July 2023, a domestic cat bit her foot under the left ankle joint. An enzyme-linked immunosorbent assay of blood for Bartonella henselae was prescribed and positive IgM and IgG antibodies were detected. Considering the presence of adenopathy, a cat's bite in the anamnesis, a positive serological test, and the exclusion of other causes, the diagnosis was established: Cat scratch disease, subclinical form. Lymphedema of the left lower limb, stage II-III. In addition to the vascular surgeon's recommendations – compression stockings, lymphatic drainage massage, the patient was prescribed: bicillin-5 (benzathine penicillin with procaine penicillin sterile salt) 1,500,000 units IM once every 4 weeks, for 6 months. Conclusion. Bartonella henselae infection should be considered in all cases of lymphadenitis and lymphedema of unknown etiology for timely diagnosis and antibiotic treatment at the initial stage of the cat scratch disease.